(3GdeSFhdjI GdLfGFjI Yf GdYedjGJ GdeUQajI GdGdcJQhfjI (B: s (3OQGSI ebGQfI (B/ s - (3GdUHGM YTQi CMeO efUhQ s; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JgOa GdOQGSI Edi JbOje CWQhMI JSge ai ESHGZ GdMeGjI GdLfGFjI Ydi GdYedjGJ GdeUQajI GdEdcJQhfjI VO GdCfTWI GdGLQGejI GdeSJMOKI hGdeUGMHI dJZdZd GdKhQI GdeYdheGJjI aj GdYedjGJ GdeUQajI hSf GdbhGfjf GddGReI dPdc hOb fGbhS GdNWQ hdaJ GfJHGg GdeTQY Edi GdeNGWQ hGdJgOjOGJ hGdYhGbH GdLSjeI GdeJQJHI Ydi JQc Jdc GdCfTWI GdELQGejI Ohf VHWgG hEMcGe GdSjWQI GdbGfhfjI YdjgG hCKQ Pdc Ydi GdHfhc GdEdcJQhfjI hYedGFgG HUaI NGUI hGdaQO hGdeLJeY HUaI YGeI hhVY GdMdhd GdefGSHI dgG(B: (3hHjGf QCi Gdabg hGdbVGA hGdJTQjY GdebGQf aj GdeSCdI eMd GdHMK hGdehba GdeUQj efgG heG jSJhLH Ydjg Yedg ai GdeSJbHd (B. (3hdYd eG ffTOg ef gPg GdOQGSI Cf JSGge aj aJM BaGb LOjOI hMdhd deTcdGJ hGbYjI hEVGaI JYOjdGJ Ydi GdCfXeI GdbGfhfjI GdMGdjI h JYOjdgG ef CLd ejdGO fXGe LfGFj QGOY jMej GdMbhb hjfTQ GdYOd Hjf CaQGO GdeLJeY(B: (3hCNjQkG JMGhd GdOQGSI Cf JSge hdh HLgO eJhGVY jVGa Edi GdGSgGeGJ GdLdjdI GdSGHbI ddabg ai EMOGK GdeRjO ef GdJcGed ai OGFQI GdHMhK GdLGeYjI ddeYdheGJ hGdMbGFb GdeSJeOI ef GdJLGQH ai GdOhd GdJi JeJ GdebGQfI Hjf CfXeJgG eMd GdOQGSI (B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B480-513s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdCfTWI GdGLQGejI GdeSJMOKIs; (3GdYedjGJ GdeUQajI GdGdcJQhfjIs; (3GdeSFhdjI GdLfGFjIs; (3GdJRhjQ GdeYdheGJjs; (3GdGMJjGd GdGdcJQhfjs; (3HWGbI GdGFJeGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs